Intrapartum management of a longitudinal vaginal septum - Velásquez-Rimachi, Víctor (2020)
The longitudinal congenital vaginal septum (LCVS) is a defect that can be associated with dyspareunia or dystocia during childbirth. We present a case of a 20 year old woman in whom a LCVS was identified during labor. In the pelvic examination, an elastic structure was felt about 2 cm behind the vaginal intro. During the second stage of labor, a medial section of the septum was made allowing the birth of a live female product. In conclusion, a thorough physical examination is enough to show the presence of a vaginal septum. However, there is a probability of an intrapartum diagnosis of LCVS therefore gynecological medical training is necessary to minimize the risks associated with childbirth.